Crowdfunding Syariah dan Celah Kepatuhan: Antara Fatwa dan Fakta - Vivi Khoirunnisa; Fitri Utami (AL-IQTISHAD: Jurnal Ekonomi, 2026)
This study aims to analyze the compliance of Islamic fintech crowdfunding practices in Indonesia with Sharia principles and national regulations, particularly DSN-MUI Fatwa No. 117/DSN-MUI/II/2018 and POJK No. 57/2020. A qualitative-comparative approach was employed through case studies on four Islamic fintech platforms: Ammana, DanaSyariah, Qazwa, and Ethis. Data were collected through document analysis, terms of service. The findings reveal that although all platforms claim to comply with Sharia standards and regulations, potential deviations exist in practice, such as fixed-return arrangements, unclear contract structures for inexperienced investors, and possible conflicts of interest due to the platforms' dual roles. While digital technologies enhance efficiency, they are not yet supported by adequate Sharia literacy. The study concludes that Islamic crowdfunding fintech holds great potential to support MSME financing fairly and inclusively, but requires improved education, contract transparency, and Sharia-based risk mitigation innovation.